a Student Perceptions of Madura State Polytechnic Health Department on Covid 19 Vaccination - Abdan Syakura; Edy Suryadi Amin; Endang Fauziyah S (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Introduction: There are still many people who are against the vaccine even though it has gone through the clinical trial stages according to the standard. Students are agents of change. Students as part of the public's mind are expected to be able to become pioneers of successor to health information sources to the community. This study aims to determine Student Perceptions of the Madura State Polytechnic Health Department on Covid 19 Vaccination. Methods: The design used in this study was a descriptive design. The population in this study were all students of level I, II and III academic year 2021-2022, Madura State Polytechnic Health Department, taken using a sampling technique using a non-probability cluster sampling technique. Data analysis used descriptive data analysis, descriptive data analysis explained the indicators of questionnaire analysis of each variable. Results: The results showed that most of the students of the Department of Health (94%) had a positive perception of the covid-19 vaccination. Conclusion: Students as part of the academic community are one of the important aspects in changing behavior in people's lives. Students are the delivery of information as well as part of the component of delivering good, correct, and educative information to the community. Positive student perceptions about vaccination and prevention of transmission as well as improving healthy lifestyles are expected to be able to provide more value in the development of public health status